Penerapan Model Pembelajaran Blended Learning dalam Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan - Marsel Nande; Wati Ahmad Irman (Universitas Pahlawan Tuanku Tambusai, 2021)
The purpose of this study, namely to improve student learning outcomes in the subject of ledger class XA Accounting at SMK Negeri 1 Ende through the application of blended learning. This type of research used in this research is classroom action research (CAR). The subjecs of this research were 32 students of class XA SMK Negeri 1 Ende. At the same time, the data collection techniques used in this study were: (1) testing, (2) observation, (3) documentation. The research data obtained were analyzed descriptively using simple descriptive statistics. Based on the findings of researchers that learning Basic Accounting, Ledger teaching materials have been done well. In the cognitive domain, it was 18.64% from cycle I to cycle II. In the affective domain, it was 58.90% from cycle I to cycle II. Meanwhile, the psychomotor domain was 27.72% from cycle I to cycle II.